Sosialisasi Peningkatan Literasi Ekonomi Syariah Terhadap Kader Akademisi Santri Ponpes Al-Islahiyyah Singosari Malang - Sri Muljaningsih; Dwi Retno Widiyanti; Asyila Muthi’ah; Nanik Shofiatin; Dinda Rahmah Wardhani; IKA ANGGRAINI (CV. Multi Kreasi Media, 2022)
Along with the continuous development of the times, Islamic boarding schools are currently facing developments not only as Islamic learning institutions but are also required to follow the flow of developments in science and technology (IPTEK). This makes pesantren experience a paradigm shift from an institution that is only centered on deepening religious knowledge, but also becomes an institution for developing economic potential. The concept of the role of students in the development of Islamic economics is very interesting to discuss, because students who are busy every day with learning activities or the Koran both in Islamic boarding schools and in formal schools. By nurturing sharia economic cadres from an early age in Islamic boarding schools, it is hoped that many students will engage in sharia economics, both in the realm of Islamic finance, Islamic entrepreneurship or Islamic philanthropic institutions such as amil zakat, infaq, sadaqah and waqf institutions. The method used) is through guidance in an effort to improve Islamic Economic Literacy in students of Al-Ishlahiyah Islamic Boarding School, Singosari, Malang. Through five stages, namely observation, collaborating with Al-Ishlahiyah Islamic Boarding School, making preparations for sharia economic guidance, implementing sharia economic guidance, and evaluating. The material contains a basic understanding of Islamic economics and an overview of lectures in the Islamic economics study program. The service activities carried out resulted in increased knowledge about Islamic economics and the interest of students to continue studying in the Islamic economics study program.